Collaboration with community connectors to improve primary care access for hardly reached people: a case comparison of rural Ireland and Australia - Carolyn Wallace; Jane Farmer; Carolynne White; Anthony McCosker (BMC, 2020)
Abstract Background This study presents a way for health services to improve service access for hardly reached people through an exploration of how staff can find and collaborate with citizens (referred to as connectors) who span socio-cultural boundaries in their community. The study explored the local socio-cultural contexts of connectors' boundary spanning activities and if they are health related; boundary spanning occurring between connectors and health professionals at the interface of health systems and community; and the opportunities and barriers to actively seeking out and collaborating with community connectors to access marginalised and hardly reached people. Methods We conducted a qualitative case comparison from rural Ireland and Australia. Following purposive snow-ball sampling techniques to recruit participants, semi-structured interviews were conducted with 34 community informants, 21 healthcare staff and 32 connectors. Transcripts were coded and analysed using an inductive approach to ascertain categories and overall themes. Results We found a diverse sample of connectors relating to heterogenous, small and locally distinct groups of hardly reached people. Overall 26 connectors were active at the interface between health services and the community, with variation in how this occurred between cases. The majority (21) described one or more health related activities with hardly reached people. All connectors expressed a willingness to develop a relationship with local health services on issues they identified as relevant. Barriers to collaborations between connectors and health services related to bureaucracy, workload, and burnout. Conclusions Collaborating with connectors has potential as one strategy to improve access to health services for hardly reached people. To enact this, health staff need to identify local socio-cultural boundaries and associated connectors, facilitate two-way connections at the boundary between health services and community and enable collaboration by attending to activities in the community, at the interface between health services and community, and within the health system.